2020
DOI: 10.1016/j.ejrad.2020.109305
|View full text |Cite
|
Sign up to set email alerts
|

Arterial calcification and long-term outcome in chronic limb-threatening ischemia patients

Abstract: Within five years after presentation 50-60% of patients with chronic limb-threatening ischemia (CLI) have died or had an amputation. We assessed the predictive value of lower extremity arterial calcification on computed tomography (CT) characteristics on both 7-years amputation-free survival and 10-years all-cause mortality in patients with CLI. Method: Included were 89 CLI patients (mean age 73.1 ± 11.6 years) who underwent a CT angiography of the lower extremities. In the femoropopliteal and crural arteries … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…In this study, the CLLA of the operated limb was a good predictor for 10 year all-cause mortality. 15 In accordance with other perioperative risk stratification scores, 16 our findings corroborate the CSOL as another preoperative variable to assist in patient treatment.…”
Section: Discussionsupporting
confidence: 84%
“…In this study, the CLLA of the operated limb was a good predictor for 10 year all-cause mortality. 15 In accordance with other perioperative risk stratification scores, 16 our findings corroborate the CSOL as another preoperative variable to assist in patient treatment.…”
Section: Discussionsupporting
confidence: 84%
“…Recently, we also showed that CLI patients with complete annular calcifications in the lower extremity had a significantly worse all-cause mortality compared to the group without complete annular calcifications [25]. Another study has shown that patients with a higher degree of annular calcification in the abdominal aorta are associated with a higher all-cause mortality (29).…”
Section: Discussionmentioning
confidence: 87%
“…Patients with CLI are more likely to have extensive calcification of the media, often encompassing the whole vessel circumference [ 21 ]. Extensive MAC is independently associated with an increased 10-year mortality risk and risk of limb amputation [ 22 ]. The extension of medial calcification is associated with an increased mortality risk, irrespective of the revascularization method used [ 23 ].…”
Section: Clinical Relevance Of Mac In Patients With Padmentioning
confidence: 99%